ATTERBERG LIMIT DAN DIRECT SHEAR STRENGTH TANAH LEMPUNG DENGAN SPENT CATALYST RCC-15 DAN Ca(OH)2 - Anita Setyowati Srie Gunarti; Elma Yulius (Universitas Islam 45, 2015)
Improvement of physical and mechanical properties of the soil should be used if it is found that the soil does not meet the technical requirements to be used as supporting building or street. Therefore, before it is used as a building support, need further research on soil stabilization. In this study used the waste from UP VI Pertamina Balongan Indramayu produced large enough that Spent Catalyst RCC 15 combined with Ca (OH) 2 or commonly referred to as the lime stabilization of clay material. Waste Utilization of Spent Catalyst RCC 15 which reaches 20 tons / day course will reduce the burden will even eliminate the cost of management, otherwise will bring significant benefits. One method of stabilization of soil chemical stabilization as an effort to increase strength, reduce the decline, and improve the physical and mechanical properties. In this study, chemical stabilization method is used to test the Atterberg Limits and Direct Shear on native soil and soil stabilized with lime Spent Catalyst 3% and 1.5%, 3%, 4.5% were cured for 7 days . The addition of Ca(OH)2 and Spent Catalyst RCC 15 on clay is able to change the value of the land for the better plasticity. The increase in the value of the friction angle and cohesion shown in optimum soil stabilization with lime content Spent Catalyst 3% and 1.5%. Cohesion has increased by 3.2% and the angle of friction in an increase of 27.3%. Key Words: Spent Catalyst RCC 15, Ca(OH)2, Soil Stabilization, Direct Shear Strength, Atterberg Limit.